2018
DOI: 10.1002/cjoc.201800237
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Direct Coupling of Allylic Alcohols with Organoboron Reagents

Abstract: The direct coupling of allylic alcohols with arylboronic acids or their derivatives catalyzed by Ni(cod)2 in the presence of a catalytic amount of base has been developed. A wide variety of allylic substrates or arylboronic acids turned out to be applicable to this catalytic system. The present method does not require the use of ligands for stabilizing the nickel catalyst in most cases or additional activators for activation of allylic alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In the optimization of reaction conditions, we noticed that the reduced stoichiometry of aryl boronic acids would result in lower yield. Based on the literature reports, 27 we proposed a plausible reaction mechanism for this Pd-catalyzed coupling between 1a−c and boronic acids (Scheme 5). Initially, the allyl alcohol moiety in α-hydroxymethyl cycloenones (1) was activated by Lewis acidic boronic acid (2), which weakened the C−O bond via intermediate A.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…In the optimization of reaction conditions, we noticed that the reduced stoichiometry of aryl boronic acids would result in lower yield. Based on the literature reports, 27 we proposed a plausible reaction mechanism for this Pd-catalyzed coupling between 1a−c and boronic acids (Scheme 5). Initially, the allyl alcohol moiety in α-hydroxymethyl cycloenones (1) was activated by Lewis acidic boronic acid (2), which weakened the C−O bond via intermediate A.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…Liu and co-workers used Ni(cod) 2 without any additional ligand to catalyze the allylic arylation of arylboronic acids and allyl alcohols (Scheme 16C). 29 Screening of the catalytic system showed that a combination of Ni(cod) 2 with phosphine ligands such PPh 3 , PMe 2 Ph, PBu 3 , or the bidentate dppp, and dppf as well as bipyridyl and IPr ligand could promote the transformation of cinnmamyl alcohol and 4-…”
Section: Scheme 15 Proposed Mechanism For Linear--selective Allyl-almentioning
confidence: 99%
“…-Biphenyl]-4-yl)-4-methylpent-3-en-2-ol (6). According to method A, 1.9 mL of n-butyllithium (1.6 M, 31 mmol) was slowly added to a solution of 4-bromobiphenyl (699 mg, 3 mmol) dissolved in an anhydrous diethyl ether (0.20 M) and precooled to −78 °C.…”
Section: -([11′mentioning
confidence: 99%
“…Allylic alcohols are indispensable functional groups in the synthesis of structurally complex organic molecules. 3,3′-Disubstituted allylic alcohols, in particular, are often more difficult to synthesize than their monosubstituted counterparts. Though methods such as the conjugate addition of nucleophiles to ynones and the addition of organometallic reagents to propargylic alcohols have been described, one method that has received little attention is the 1,3-migration of the hydroxy group in tertiary allylic alcohols.…”
Section: Introductionmentioning
confidence: 99%